1986
DOI: 10.1037/0735-7028.17.6.504
|View full text |Cite
|
Sign up to set email alerts
|

Ethical considerations of social/romantic relationships with present and former clients.

Abstract: The chairpersons of the state and provincial ethics committees and the executive directors of licensing boards were surveyed in regard to the frequency of complaints of sexual impropriety filed against psychologists during 1982 and 1983. The survey also concerned the disposition of the complaints and whether the psychologist alleged that the therapeutic relationship had terminated before the initiation of the sexual relationship. The findings indicated that a considerable number of complaints had been filed, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…One course in ethics is clearly insufficient to address all topics psychologists are likely to face throughout their careers, and these concerns should be addressed in other courses and mentoring situations as well (Sell, Gottlieb, & Schoenfeld, 1986). The ethical issues facing those in the mental health field are complex, and they arise even in graduate school, where the student is introduced into multiple roles as protégé, student, supervisee, or supervisor of others in research and teaching settings.…”
Section: Implications and Recommendationsmentioning
confidence: 97%
“…One course in ethics is clearly insufficient to address all topics psychologists are likely to face throughout their careers, and these concerns should be addressed in other courses and mentoring situations as well (Sell, Gottlieb, & Schoenfeld, 1986). The ethical issues facing those in the mental health field are complex, and they arise even in graduate school, where the student is introduced into multiple roles as protégé, student, supervisee, or supervisor of others in research and teaching settings.…”
Section: Implications and Recommendationsmentioning
confidence: 97%
“…In terms of administrative or civil actions, Sell, Gottlieb & Schoenfeld (1986) and Gottlieb, Sell & Schoenfeld (1988) found that relatively few boards and associations had developed guidelines on the permissibility of post-termination relationships. There is, however, one specific reference to PTSRs in the 1990 Code of Conduct adopted by the Association of State and Provincial Psychology Boards.…”
Section: Legal and Clinical Considerations Related To Ptsrs And Ptbrsmentioning
confidence: 99%
“…Such statistics provide only a small sample of the large and growing body of work that addresses issues of abuse. For more detailed and comprehensive information regarding the types of abuse studied in this survey, representative research reports, reviews of issues and findings, and discussions of implications are provided by Briere (1991); Brodsky (1989); L. S. Brown (1988); G. R. Brown and Anderson (1991); Council on Ethical and Judicial Affairs, American Medical Association (1991); Council on Women in Psychology (1989); Courtois (1988); Estrich (1987);Feldman-Summers (1989); Feldman-Summers and Jones (1984); Finkelhor (1984); Fitzgerald (1991);Fitzgerald and Ormerod (1991); Fitzgerald et al (1988); Frieze (1986); Gartrell, Herman, Olarte, Feldstein, and Localio (1989); Gechtman (1989); Gutek (1985, in press); Herman (1981); Holroyd and Brodsky (1977); Koss and Harvey (1991); Pope (1990aPope ( , 1990b; Rubin and Borgers (1990); Russell (1986); Sell, Gottlieb, and Schoenfeld (1986); Shopland and VandeCreek Note. Ratings ranged from 1 (very poor; e.g., little or no attention devoted to the topic) to 5 (very good).…”
Section: History Of Abusementioning
confidence: 99%